Constellations of Power and Authority in the Political Economy of Illegal Timber Extraction in BTAD, Assam. (August 2017) - Dutta, Anwesha; Suykens, Bert
This article seeks to comprehend the way the illegal timber economy in the Bodoland Territorial Autonomous Council (BTAD) in Assam is integrated within a constellation of power and authority. Based on over ten months of ethnographic field research, our analysis shows that the timber trade is indeed characterized by what can be conceptualized as an excess of sovereignty. However, a burdened agency is still exercised by those in the timber trade. Moreover, the authority structure consisting of state, rebel and non-armed actors do not directly engage violently in the trade, but are more interested in taxation, governance, or indeed wildlife protection, showing the other side of this multiple authoruty structure. As the article shows, different ethnic groups, which are often thought to be diametrically opposed to each other, collaborate in the local timber commodity chain. However, these collaborations are characterized by highly unequal relations of exchange. As we argue, those that have preferential access to the authority structure can use this to dictate the terms of interaction. Finally, while the timber economy is usually characterized by the operation of the constellation of power and authority, there are interstitial moments where the (violent) interactions among the actors embeded in the structure weaken the direct territorial control by them. As a result, times of violence are often also those in which the trade can flourish.